Epidemiological trends of urolithiasis in working-age populations: Findings from the global burden of disease study 1990–2021 - Weitao Yao; Xin Wei; Qiang Jing; Xiaobin Yuan; Fan Liu; Xuhui Zhang (PLoS ONE, 2025)
Background One of the most prevalent urinary disorders worldwide, urolithiasis has symptoms and a high rate of recurrence. It has placed a significant strain on the global economy and health care system, particularly among those aged 20–54. Comprehensive research on the global burden and evolving trends of urinary calculi in the 20–54 age range is lacking. Methods Three important urolithiasis indicators—prevalence, incidence, and Disability-Adjusted Life Years (DALYs)—were used from the Global Burden of Disease (GBD) database between 1990 and 2021 for this study.Point estimates were provided, as well as 95% uncertainty intervals (UIs).. To assess trends in the burden of urolithiasis among the 20–54 age range, we used percentage change and estimated annual percentage change (EAPC). The time trends from 1990 to 2021 were thoroughly examined using joinpoint regression analysis. This method makes it possible to compute the annual percent change (APC) and average annual percent change (AAPC), as well as the 95% Confidence Intervals (CIs)that go with them. Results The number of patients, cases, and DALYs linked to urinary stones among people aged 20–54 has significantly increased worldwide. For example, the number of urolithiasis cases increased by 48%, from 1,576,704 in 1990–2,335,010 in 2021. Comparably, the number of new cases increased by 47%, from 42,272,855 in 1990–62,269,033 in 2021. Between 1990 and 2021, the number of DALYs rose from 218,150–290,210, representing a roughly 33% increase. As of 2021, intermediate sociodemographic index (SDI) regions had the highest DALY rates, while medium-high SDI regions had the highest prevalence and incidence rates among the five SDI regions examined for this time period. Individuals between the ages of 50–54 had the greatest incidence rate within the designated cohort for that year, followed by those between the ages of 45–49 and 40–44. Across all age groups, there were noticeable gender differences, with males showing significantly greater rates than girls. Conclusions Overall, over the past 32 years, the prevalence of urolithiasis among people aged 20–54 has increased dramatically worldwide, especially in low-SDI nations and among those aged 50–54. With the goal of reducing the social and medical cost and enhancing the working-age population’s quality of life and productivity, the study’s findings highlight the urgent need for focused intervention techniques to prevent and treat urolithiasis in this age group. For example, in middle – high SDI areas, encourage 3 liters of water and a low – salt diet daily, especially for the over - 50s. In middle SDI areas, enhance primary care diagnostics, like using portable ultrasound. Regular screenings should be set for males in high – risk jobs, such as heat – exposed ones. However, this GBD – based study has limitations like data uncertainty, insufficient local strategies, and lack of trend tracking.